Pemanfaatan Biji Ketapang Sebagai Bahan Alternatif Pembuatan Tahu Dengan Lama Perendaman Dan Koagulan Yang Berbeda - Rohayati, Meiliasari, Dra. Hj. Suparti, M.Si (2015)
Catappa seed contains 23,78% protein, 16.02% carbohydrate, 4,27% ash, 4,13, water, 4.94% fiber, 51.80% fat dan 548,78 Kkal. Catappa seed contains high protein, so that it can be used in tofu production. The research purpose is to know protein substance and organoleptic quality of Catappa . the writer uses completely Randomized Design as the research method contains two factor include soaking time and the inds of coagulant. Result of the research show that the highest total protein total found in the sample of Catappa during 2 hours and soaking time by using whey coagulant (J2W1) 4,469 % wb, while the lowest total protein is in 4 hours sand soaking time by using lime coagulant (J4W2) 2,224 % wb. In organoleptic test of tofu Catappa seed , treatment during 3 hours soaking time by using whey coagulant (J3W1) has characteristics quality : non acid, not smell, soft texture, cream colour, elastic and a lot of panelist like it.